Absolute Pitch and Its Frequency Range - RAKOWSKI, Andrzej; ROGOWSKI, Piotr (Archives of Acoustics, 2013)
This paper has two distinct parts. Section 1 includes general discussion of thephenomenon of “absolute pitch” (AP), and presentation of various concepts concerningdefinitions of “full”, “partial” and “pseudo” AP. Sections 2–4 include presentationof the experiment concerning frequency range in which absolute pitch appears, anddiscussion of the experimental results. The experiment was performed with participationof 9 AP experts selected from the population of 250 music students as bestscoring in the pitch-naming piano-tone screening tests. Each subject had to recognizechromas of 108 pure tones representing the chromatic musical scale of nineoctaves from E0 to D#9. The series of 108 tones was presented to each subject 60times in random order, diotically, with loudness level about 65 phon. Percentageof correct recognitions (PC) for each tone was computed. The frequency range forthe existence of absolute pitch in pure tones, perceived by sensitive AP possessorsstretches usually over 5 octaves from about 130.6 Hz (C3) to about 3.951 Hz (B7).However, it was noted that in a single case, the upper boundary of AP was 9.397 Hz(D9). The split-halves method was applied to estimate the reliability of the obtainedresults.